Maxillofacial injuries managed at Tribhuvan University Teaching Hospital, Kathmandu, Nepal: a 7 year retrospective study - K.C., Krishna; Shrestha, Jayan Man (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Of all the facial injuries, maxillofacial region is one most frequently involved. The maxillofacial region is most prone to trauma owing to its prominent position in the skull which gets involved easily in case of trauma. Facial injuries can have long term consequences in terms of esthetics and function. Few series have been studied in terms of incidence of facial trauma in Nepal. Methods: We performed a retrospective analysis of all the patients admitted and treated at the surgery and dental department of the Tribhuvan University teaching hospital with the diagnosis of facial injuries over the period of 8 years (2008 to 2016). The characteristics of these injuries were analyzed. The causes of injury were classified as follows: traffic accidents, assaults, animal attacks, falls, sports and related to the disaster. Anatomically, fractures of the mandible were classified into following regions: symphysis, parasymphysis, canine, body, angle, condyle and fractures more than one site (multiple sites). Midface fractures were classified according to the Le fort classification into Le fort I, Le Fort II, Le fort III and ZMC. Results: A total of 133 patients with facial fractures were treated between 2008 and 2016 which were retrospectively analyzed. The male: female ratio was 2:1 and the largest subgroup of patients were between 16 and 30 years of age. The most common cause of injury was road traffic accidents (62.4%) involving motorcycles or automobiles. Other common causes included, in descending order, falls (5.2%), animal attacks (5.2%) assaults (3.7%) and sports. Isolated mandibular fractures were most common (50.4%), followed by isolated Zygomaticomaxillary complex (ZMC) fractures (18.8%). The percentage of fractures involving Le fort I was 8.3%, and that of isolated alveolar fractures was 9%. Conclusion: RTAs remains the main cause for maxillofacial injuries where males were predominately affected, condition of the roads, traffic regulations and adverse weathers all contribute to the TRAs in developing countries like Nepal.